2020
DOI: 10.3390/f11020217
|View full text |Cite
|
Sign up to set email alerts
|

Fire Suppression Resource Scarcity: Current Metrics and Future Performance Indicators

Abstract: Wildland fire occurrence is highly variable in time and space, and in the United States where total area burned can vary substantially, acquiring resources (firefighters, engines, aircraft, etc.) to respond to fire demand is an important consideration. To determine the composition and scale of this set of suppression resources managers may utilize data produced by past supply and demand information. The key challenge with this approach is that there is currently no clear system of record to track suppression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 23 publications
(38 reference statements)
0
31
0
Order By: Relevance
“…Disease outbreaks could also affect the ability of the firefighting community to respond to multiple fires in an active season (Thompson et al, 2020). Large wildfires have been the norm in recent years and resources have been strained when several fires occur simultaneously (Belval et al, 2020). Infected personnel who leave a fire are not easily replaced or worse; infected but asymptomatic individuals may leave one fire and spread the infection to another camp.…”
Section: Discussionmentioning
confidence: 99%
“…Disease outbreaks could also affect the ability of the firefighting community to respond to multiple fires in an active season (Thompson et al, 2020). Large wildfires have been the norm in recent years and resources have been strained when several fires occur simultaneously (Belval et al, 2020). Infected personnel who leave a fire are not easily replaced or worse; infected but asymptomatic individuals may leave one fire and spread the infection to another camp.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, statistical significance should not be conflated with practical significance (Daniel 1977), and the changes in simultaneity reported in the present study may not represent changes that are relevant to firefighting planning and management. Future work should further validate the appropriateness of using peak simultaneity to infer broader trends about resource demand (Belval et al 2020), and identify what other factors may be Fig. 8.…”
Section: Peak Simultaneitymentioning
confidence: 99%
“…For example, private engines (Lyon et al 2017) and air tankers (Thompson et al 2013) have been dispatched more frequently in recent years than they have historically. Requests for large air tankers are increasingly returned as 'unable to fill', suggesting increasing levels of resource scarcity during periods of high wildfire activity (Belval et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…ROSS is the primary database used to track orders and assignments of wildland fire suppression resources on large fires and intraregional resource requests (i.e., requests for resources where the resource must come from outside the home unit or a neighboring unit to respond to the incident) (https: //famit.nwcg.gov/applications/ROSS). Designed for use by dispatchers, the ROSS is the most complete source of standardized information regarding resource ordering in the US (see Belval et al [23] for data quality issues). The ICS-209 does contain information about resources committed to fires.…”
Section: Datamentioning
confidence: 99%
“…Bayham and Yoder [13] found that fires threatening homes are dispatched more Type 1 Crews and Engines, which reduces the likelihood that other simultaneously burning fires will receive requested resources. Belval et al (in review) [23] examined the metrics for quantifying resource use and scarcity on a national (rather than incident) level for Type 1 crews and large airtankers, finding substantial differences between patterns of Type 1 crew and large airtanker usage and scarcity.…”
Section: Introductionmentioning
confidence: 99%